Molecular, cellular and histological changes in skin from a larval to an adult phenotype during bony fish metamorphosis - Campinho, Marco António (2014)
Developmental models for skin exist in terrestrial and amphibious vertebrates but there is a lack of information in aquatic vertebrates. We have analysed skin epidermal development of a bony fish (teleost), the most successful group of extant vertebrates. A specific epidermal type I keratin cDNA (hhKer1), which may be a bony-fishspecific adaptation associated with the divergence of skin development (scale formation) compared with other vertebrates, has been cloned and characterized. The expression of hhKer1 and collagen 1α1 in skin taken together with the presence or absence of keratin bundle-like structures have made it possible to distinguish between larval and adult epidermal cells during skin development. The use of a flatfish with a well-defined larval to juvenile transition as a model of skin development has revealed that epidermal larval basal cells differentiate directly to epidermal adult basal cells at the climax of metamorphosis. Moreover,hhKer1 expression is downregulated at the climax of metamorphosis and is inversely correlated with increasing thyroxin levels. We suggest that, whereas early mechanisms of skin development between aquatic and terrestrial vertebrates are conserved, later mechanisms diverge.